Penerapan Audit Internal pada Organisasi Perangkat Daerah - Adinda Sinlaeloe; Frescilia Polin; Sonya Laho’an; Agnes Tukan; Olivia De Jesus; Susana Purnamasari Baso (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The effectiveness of internal audit remains a critical issue in Regional Government Organizations (OPD), particularly in ensuring accountable and transparent financial management. In practice, internal audit functions often face limitations related to auditor competence, institutional support, and follow-up of audit recommendations. This study aims to examine the implementation of internal audit in OPD, analyze audit procedures conducted by Regional Inspectorates, and identify key factors influencing audit effectiveness. The research employs a qualitative descriptive approach through a structured literature review. Data were collected from scientific journals, government regulations, books, and prior empirical studies, and analyzed using content analysis to identify recurring themes and patterns. The results indicate that internal audit plays a significant role in strengthening internal control systems, improving regulatory compliance, and enhancing the reliability of financial reporting in local governments. The Regional Inspectorate conducts various audit activities, including financial audits, performance audits, specific-purpose audits, evaluations, reviews, and monitoring. However, audit effectiveness is constrained by limited budgets, uneven auditor competencies, weak information system integration, and administrative challenges. Strengthening auditor capacity, improving institutional support, and ensuring leadership commitment to audit follow-up are essential to enhance the role of internal audit in regional governance.